2009
DOI: 10.1007/s11665-008-9312-7
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Thermal Analysis of the Eutectic Formed in Pb-Sn Alloys

Abstract: The effect of the presence of two different primary phases on the microstructural characteristics and solidification kinetics of Pb-Sn eutectic was analyzed using Fourier thermal analysis method (FTA) and microstructural characterization. Three Pb-Sn alloys, a hypoeutectic, an eutectic, and a hypereutectic alloy, were melted in an electric furnace under an argon atmosphere and poured into sand molds. Cooling curves were obtained and numerically processed using FTA. Microstructural observations of the probes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In these papers, FTA has been used to determine the kinetics of gray cast iron solidification in the local region. Later, the FTA method has been successfully used to characterize the solidification process for various metal alloys, such as: aluminum-based materials [10][11][12][13][14][15], magnesium alloy [16], different Pb-Sb alloys [17], and for cast-composites [18]. As it has been proven in [19], the FTA method can also be used to analyze the kinetics of thermal decomposition of resin binders intended for use in molding sands.…”
Section: Introductionmentioning
confidence: 99%
“…In these papers, FTA has been used to determine the kinetics of gray cast iron solidification in the local region. Later, the FTA method has been successfully used to characterize the solidification process for various metal alloys, such as: aluminum-based materials [10][11][12][13][14][15], magnesium alloy [16], different Pb-Sb alloys [17], and for cast-composites [18]. As it has been proven in [19], the FTA method can also be used to analyze the kinetics of thermal decomposition of resin binders intended for use in molding sands.…”
Section: Introductionmentioning
confidence: 99%
“…Gan et al reported the size effect of Sn-Pb microstructures on microdevices, and they indicated that stable microstructures are crucial in several applications [16]. The effect of the two primary phases on Sn-Pb microstructures was studied using thermal analysis method [17].…”
Section: Introductionmentioning
confidence: 99%